Optimalisasi Siklus Manajemen Kinerja untuk Pengembangan Kepemimpinan di Organisasi - Tanti Sugiharti (Journal Of Business, Finance, and Economics (JBFE), 2022)
The performance management cycle represents a critical framework for enhancing leadership development within organizations. This conceptual article proposes that by integrating comprehensive performance evaluations, feedback, and goal-setting mechanisms, the performance management cycle not only ensures operational efficiency but also fosters the cultivation of effective leadership qualities. The cycle begins with planning, where leaders define and communicate organizational goals and individual objectives. The subsequent evaluation phase offers a structured approach to assessing individual and team performance against pre-established objectives, facilitating objective leadership assessments and highlighting areas for improvement. Feedback, the final phase, is instrumental in leadership development, providing a platform for constructive dialogue, recognition of achievements, and identification of development opportunities. This literature review argues that through the systematic application of the performance management cycle, organizations can create a supportive environment for leadership development, thereby enhancing their competitive advantage and promoting a culture of continuous improvement.